EMBRYONIC STAGE OF THE MOTTLED RAY, AETOMYLUS MACULATVS (GRAY), WITH A NOTE ON ITS BREEDING SEASON - Devadoss, P (Indian Journal of Fisheries, 2011)
Developmental stage of the intrauterine embryos of Aeiomylus maculatuthas been presented. Except for the cephalic region and the presence of internalyolk the full-term embryo resembles the adult in all respects. The conditionof the uterus and the position of the embryos inside the uterus are described, and thetime of parturition discussed